Comparative Study on Mechanical and Tribological Properties of Alkali-Treated and Untreated Sida acuta Fiber-Reinforced Composite - Chandra Mohan Heggade Halli Krishnappa; Devaraj Sonnappa; Narayana Swamy Kalavara Saddashiva Reddy; Nikhil Rangaswamy; Ganesh Ravi Chate; Manjunath Patel Gowdru Chandrashekarappa (Eng)
The present study focused on a comparative analysis of NaOH-treated and untreated Sida acuta fiber-reinforced composites with respect to their wear behavior and compressive strength. The Sida acuta fibers were treated with 5% NaOH, while the untreated fibers were used directly as reinforcement, both comprising 32 ± 1 wt.% of the epoxy matrix composites. The composites were further characterized based on their average density, hardness, and compressive strength. Additionally, weight loss, volume loss, and wear rate were examined under dry wear test conditions across various loads and sliding velocities. The results indicate that the alkali-treated fiber-reinforced composite exhibits superior hardness (84.3 ± 2.0) and compressive strength (99.89 ± 3.92 MPa), representing improvements of 12.57% and 13.5%, respectively, over the untreated fiber-reinforced composite. Moreover, the 5% NaOH-treated fiber-reinforced composite demonstrated lower wear rates compared to its untreated counterpart. Scanning Electron Microscopy (SEM) was employed to examine the dry wear surface morphology of both composite laminates, providing insights that support the observed test results. Overall, the developed Sida acuta composite exhibits promising properties, making it suitable for lightweight and medium-strength structural applications.